Native entomopathogenic nematodes (Rhabditida) in four departments of Colombia - MELO-M., ELSA LILIANA; ORTEGA-O., CARLOS ALBERTO; SUSURLUK, ALPER; GAIG, ANDREAS; BELLOTTI, ANTHONY C. (Revista Colombiana de Entomología, 2009)
Entomopathogenic nematodes (EPN) of the groups Heterorhabditidae and Steinernematidae are used as potential control agents of soil pests, being found in many habitats worldwide according to studies of their distribution. We collected soil samples in four Colombian departments (Quindío, Risaralda, Caldas, and Cauca) in order to isolate and identify native EPN strains associated with whitegrub (Coleoptera: Melolonthidae) and burrower bug (Hemiptera: Cydnidae) Cyrtomenus bergi soil pests. EPN isolation was done through the Galleria mellonella (Lepidoptera: Pyralidae) bait method. After verifying the entomopathogenicity of the samples using Koch’s postulates, we multiplied, stored and identified the EPN. We analyzed 284 samples (300 g of soil each) collected in 23 sites in 15 crops. Pathogenic and saprophytic nematodes were present in 17 samples. PCR technique lead to the identification of Steinernema kraussei Steiner (Rhabditida: Steinernematidae) coming from of two samples, one from Cassava (ex Manihot esculenta L.) in Cauca and the second one from Inga spp. in Risaralda, being these the first record of the species for the country.